OOPS! Or, Designing an Intercultural Online Participatory Seminar in the Spirit of Highlander Folk School - Alexander, Ilene D.; Fink, Alexander (Proceedings of the International Conference on Networked Learning, 2016)
Seeking to build a relational, reflexive, dialogical, and praxis-oriented open, online learning space to engage intercultural teaching and learning, an experienced educator of future teachers and a graduate student in youth leadership developed an online seminar that embodied its content (intercultural, inclusive learning and teaching) in praxis. This paper outlines the process of designing the seminar, briefly examines how it functioned, and closes with ideas for exploration with NCL participants.